Comparative Study of the Effect of Crude Palm Oil on Environmental Quality with Parameters: Lux, Vibration, and Noise Levels in Engines - Nur Fadilah Rizky Supramono; Fawwaz Aqillah Nurmansyah; Muhammad Ikhsan; Erwan Adi Saputro; Wiliandi Saputro (Nusantara Science and Technology Proceedings, 2023)
Fuel is a primary component in engines used across various applications, including diesel engines. In an effort to reduce environmental impact, alternative fuels have become a focal point of Attention. One highly promising alternative fuel is Crude Palm Oil. The potential of Crude Palm Oil to reduce greenhouse gas emissions and dependence on fossil resources has made it an intriguing subject of research. However, differences in the characteristics between Crude Palm Oil and diesel fuel can affect engine performance and environmental conditions. Therefore, this study aims to determine the direct impact of using Crude Palm Oil, heated to 90°C, on environmental conditions, including Lux levels, vibration, noise levels, and engine power. Crude Palm Oil was used as the fuel, and Dexlite was used as the comparative fuel. Testing was conducted over a 56-hour operational period, with a constant load of 4 kW and a constant engine RPM of 2200. The research findings indicate that engines running on Crude Palm Oil produce lower Lux levels compared to those using Dexlite. Through a series of three-point tests, it was observed that Dexlite produced Lux values 3,9%, 26,12%, and 59,36% higher than Crude Palm Oil. This difference is due to the lower power output of Crude Palm Oil-fueled engines, approximately 24% lower than Dexlite-fueled engines. Additionally, engines fueled by Crude Palm Oil exhibited vibrations 10,07%, 7,14%, and 5,11% higher at the three measurement points, along with noise levels 1,8%, 1,08%, and 1,15% higher. These differences can be attributed to the distinct characteristics of the two fuels, highlighting their impact on engine performance and environmental conditions. It is clear that the choice of fuel type significantly affects Lux parameters, vibration, and noise levels, with Dex lite emerging as the superior option in terms of noise reduction and lighting intensity due to its higher power output.